Humiliation, degradation, dehumanization human dignity violated - Kaufmann, Paulus; Kuch, Hannes 1978-; Neuhaeuser, Christian; Webster, Elaine (Library of ethics and applied philosophy, 2011)
Degradation, dehumanization, instrumentalization, humiliation, and nonrecognition ? these concepts point to ways in which we understand human beings to be violated in their dignity. Violations of human dignity are brought about by concrete practices and conditions; some commonly acknowledged, such as torture and rape, and others more contested, such as poverty and exclusion. This volume collates reflections on such concepts and a range of practices, deepening our understanding of human dignity and its violation, bringing to the surface interrelationships and commonalities, and pointing to the values that are thereby shown to be in danger. In presenting a streamlined discussion from a negative perspective, complemented by conclusions for a positive account of human dignity, the book is at once a contribution to the body of literature on what dignity is and how it should be protected as well as constituting an alternative, fresh and focused perspective relevant to this significant recurring debate. As the concept of human dignity itself crosses disciplinary boundaries, this is mirrored in the unique range of perspectives brought by the book's European and American contributors ? in philosophy and ethics, law, human rights, literature, cultural studies and interdisciplinary research. This volume will be of interest to social and moral philosophers, legal and human rights theorists, practitioners and students